KUALITAS PELAPORAN KEUANGAN PADA USAHA BISNIS APOTEK DI KOTA DENPASAR - Ni Nyoman Ayu Suryandari; Veronica Me'e (Jurnal Widya Akuntansi dan Keuangan, 2019)
The existence of a pharmacy that has two functions, namely health services and business or companies are in dire need of financial statements. From the financial statements, the financial and economic conditions of a company or pharmacy can be known. This study aims to reexamine the influence of leadership ethics variables, internal audit function and level of understanding of accounting on the quality of financial reporting. The sample in this study were 35 people who worked as a maker of pharmacy financial statements in Denpasar City. Determination of the sample using purposive sampling method and the test equipment used is multiple linear regression analysis. The results showed that the leadership ethics variable had no effect on the quality of financial reporting in the pharmacy business business as indicated by a significance value of 0.141. The variable internal audit function does not affect the quality of financial reporting in the pharmacy business in Denpasar City which is indicated by a significance value of 0.281, while the variable level of accounting understanding has a positive effect on the quality of financial reporting in the pharmacy business in Denpasar which is indicated by a significance value of 0.043.